Experimental investigation of diesel engine fuelled with different alkyl esters of Karanja oil. (1st September 2020) - Verma, Puneet; Dwivedi, Gaurav; Behura, Arun Kumar; Patel, Devendra Kumar; Verma, Tikendra Nath; Pugazhendhi, Arivalagan
Highlights: Characteristics of Karanja biodiesel obtained from different alcohols are studied. Biodiesels fuel emits lower CO2 emission than with diesel fuel. BSFC for biodiesel and its blends were higher compared to diesel fuel. KOPnE20 perform better engine performance than with other biodiesel blends. Abstract: The rising pollution levels resulting from vehicular emissions and limited reserves of petroleum based fuels have left mankind in pursuit of alternatives to diesel. There have been stringent regulations generated by authorities around the world regarding vehicular emissions from internal combustion engines. To this end, researchers have been exploring different sources of alternative fuels such as biodiesel produced from non-edible oil sources such as Karanja, Jatropha accompanied by the alcohol fuels, methanol, ethanol, butanol and propanol. This work has experimentally investigated the impacts of various blends of Karanja biodiesel with a chain of fewer alcohols (ethanol, 2-propanol, methanol, 1-butanol and 1-pentanol) to identify the potential of higher alcohols in the production of biodiesel and application to the diesel engine. The results showed that the brake thermal efficiency was decreased by 3.3%, while an increased brake specific fuel consumption was recorded for KOPnE20 by 11.75% compared to the mineral diesel fuel, which could be attributed to the higher calorific values of the respective fuels. The emission results indicated that the carbon dioxide emission increased by 32.25% while the nitrogen of oxide emission decreased by 6.72% for KOPnE20 compared to the diesel fuel at full load condition.